Ultraviolet Radiation and Chronic Inflammation—Molecules and Mechanisms Involved in Skin Carcinogenesis: A Narrative Review - Magdalena Ciążyńska; Irmina Olejniczak-Staruch; Dorota Sobolewska-Sztychny; Joanna Narbutt; Małgorzata Skibińska; Aleksandra Lesiak (Life, 2021)
The process of skin carcinogenesis is still not fully understood. Both experimental and epidemiological evidence indicate that chronic inflammation is one of the hallmarks of microenvironmental-agent-mediated skin cancers and contributes to its development. Maintaining an inflammatory microenvironment is a condition leading to tumor formation. Multiple studies focus on the molecular pathways activating tumorigenesis by inflammation and indicate several biomarkers and factors that can improve diagnostic and prognostic processes in oncology and dermatology. Reactive oxygen species produced by ultraviolet radiation, oxidizers, or metabolic processes can damage cells and initiate pro-inflammatory cascades. Considering the potential role of inflammation in cancer development and metastasis, the identification of early mechanisms involved in carcinogenesis is crucial for clinical practice and scientific research. Moreover, it could lead to the progress of advanced skin cancer therapies. We focus on a comprehensive analysis of available evidence and on understanding how chronic inflammation and ultraviolet radiation can result in skin carcinogenesis. We present the inflammatory environment as complex molecular networks triggering tumorigenesis and constituting therapeutic targets.